2022
DOI: 10.1210/endocr/bqac162
|View full text |Cite
|
Sign up to set email alerts
|

Metformin's Impact on the Microvascular Response to Insulin

Abstract: Metformin improves insulin’s action on whole body glucose metabolism in various insulin-resistant populations. The detailed cellular mechanism(s) for its metabolic actions are multiple and still incompletely understood. Beyond metabolic actions, metformin also impacts microvascular function. However, the effects of metformin on microvascular function and microvascular insulin action specifically are poorly-defined. In this mini-review, we summarize what is currently known about metformin’s beneficial impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Thiazolidinediones (TZDs) enhance insulin sensitivity in skeletal muscle, liver, and adipose tissue and promote fat redistribution from liver and skeletal muscle to adipocytes [ 58 , 59 , 60 ]. Metformin, the most commonly prescribed drug for diabetes, may also increase insulin sensitivity in peripheral tissues during fasting [ 61 , 62 , 63 , 64 , 65 , 66 ]. One of the mechanisms thought to be behind the protective effect of phenolic compounds on the T2DM is that OLE may increase glucagon-like peptide-1 (GLP-1) secretion both in vivo and in vitro [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones (TZDs) enhance insulin sensitivity in skeletal muscle, liver, and adipose tissue and promote fat redistribution from liver and skeletal muscle to adipocytes [ 58 , 59 , 60 ]. Metformin, the most commonly prescribed drug for diabetes, may also increase insulin sensitivity in peripheral tissues during fasting [ 61 , 62 , 63 , 64 , 65 , 66 ]. One of the mechanisms thought to be behind the protective effect of phenolic compounds on the T2DM is that OLE may increase glucagon-like peptide-1 (GLP-1) secretion both in vivo and in vitro [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the TPCs found in the OLEs, hydroxytyrosol (HT) is referred to as the chief compound responsible for the biological properties of oleuropein (OLEP), mainly its high antioxidant potential [ 59 ]. HT has also been associated with innumerous favorable properties such as immuno-protective and antimicrobial activity [ 60 , 61 ], and anti-diabetic [ 62 ], anti-arrhythmic and cardioprotective [ 63 ], hypotensive and anti-atherosclerotic [ 64 ], anti-inflammatory [ 65 ], and antioxidant [ 66 , 67 , 68 ] effects. Besides HT, other phenolic compounds have shown to exhibit antibacterial effects against several strains of bacteria responsible for intestinal and respiratory infections in vitro [ 66 , 69 , 70 , 71 ], with promising results for applications as preservatives in food industry [ 23 , 62 , 72 , 73 ], in particular reducing the growth of Helicobacter pylori, which is associated with peptic ulcers and gastric cancer [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although solid evidence is still lacking, statins may also provide benefits to endothelial function and against MVD [ 56 , 57 ]. Pre-clinical studies also showed that anti-diabetic therapies, metformin especially, may preserve/restore endothelium function [ 58 , 59 , 60 , 61 ]. Understanding the mechanisms underlying MVD in PAD patients and finding new treatments and therapeutics targeting MVD specifically may help reduce symptoms and improve quality of life.…”
Section: Etiology Of Padmentioning
confidence: 99%